Analisis Indek Kegagalan Link Panjang Standar dan Modifikasi pada Struktur EBF - Musbar; Khairul Miswar; Hanif; Zulfikar (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The rapid failure of long links in EBF structures occurs at the ends of the links due to the influence of the dominant moment. The use of long links is still very relevant due to the large space openings and meeting the AISC 341 requirements is very easy compared to other links. One of the efforts made to overcome this weakness is to increase the stiffness at the ends of the standard long links. The design of the perforated plate aims to reduce the influence of residual stresses due to wider welds and to control the critical variables. The control arm with the confirmation holes is called the modified control arm. The numerical test variables for the modified long link specimens were the plate thickness (ts) and the vertical distance from the flanges to the edge of the hole in the stiffener plate (Th). The research was carried out numerically to determine the criteria for the initiation of ductile fracture based on the performance indicators of the test specimens using the comparison of failure index and PEEQ index values. The results showed that the initiation of fracture in the flanges at the ends of the beam can be delayed by the addition of double-edged stiffener plates, this can be seen from the decrease in MRI and PEEQ index values in the critical zone of the modified long beam test specimen compared to the standard long beam.